Influence of adiposity on physiological and affective responses in walking at a self-selected pace - Kleverton Krinski; Cosme Franklim Buzzachera; Bruno Vinicius Santos; Heriberto Colombo; Hassan Mohamed Elsangedy; Sergio Gregorio DaSilva; Sérgio Luiz Carlos dos Santos; Wagner de Campos (Universidade Federal de Santa Catarina, 2010)
The aim of this study was to investigate the influence of adiposity on physiological and affective responses during walking at a self-selected pace. Forty-five sedentary women were divided into three groups according to their percentage of body fat (low tertile, LT, n=15; medium tertile, MT, n=15; and high tertile, HT, n=15). Each participant completed a maximal exercise test and a 20-min bout of treadmill walking at a self-selected pace. The preferred walking speed did not differ between the groups (1.63, 1.60, and 1.47 m.sec-1 for LT, MT and HT, respectively), whereas %O2max was higher in HT (61.8%) compared to MT (55.8%) and LT (52.8%) (P< .05). Nevertheless, affective (2.36, 1.80, and 1.85 for LT, MT and HT, respectively) response were similar between the groups. These findings suggest that adiposity did influence physiological, but not affective responses, during treadmill walking at a self-selected pace in sedentary women.